Conductas prosociales y disruptivas en adolescentes como expresión de los estilos de crianza - Daniela Nickole, Bravo Vacacela (2021)
ABSTRACT Currently, there is clear visibility of violence in different age groups. The WHO considers that youth violence is a global problem since it is estimated that around the world, about 200,000 homicides occur in this group; in Ecuador, 6 out of 10 students suffered some type of school violence. This work determined the influence of parenting styles on the development of different behaviors. Therefore, strategies were developed focused on raising awareness of the impact of parenting on adolescents, reducing disruptive behaviors, and strengthening prosocial behaviors. Prosocial and disruptive behaviors as an expression of parenting styles were analyzed using a literature review type documentary study with a quantitative approach, in which 3,591 documents were consulted, of which 51 were compiled. In addition, 10 articles were submitted to the methodological quality review through the CRF-QS instrument. Obtaining that prosocial behaviors are an expression of the authoritative parenting style, which also acts as a protective factor against disruptive behaviors, and these are caused by the negligent parenting style. The effects of parenting styles are related to other factors such as culture, type of family, and socioeconomic level. It was established that prosocial behaviors are primarily present in females. Keywords: parenting styles, prosocial behavior, disruptive behavior, adolescence. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR CC: 1002091161